Laparoscopic versus open pancreaticoduodenectomy for pancreatic ductal adenocarcinoma: a propensity score matching analysis. Issue 1 (28th October 2019) - Zhou, Wentao; Jin, Weiwei; Wang, Dansong; Lu, Chao; Xu, Xuefeng; Zhang, Renchao; Kuang, Tiantao; Zhou, Yucheng; Wu, Wenchuan; Jin, Dayong; Mou, Yiping; Lou, Wenhui
Abstract: Background: A growing body of evidence supports the use of laparoscopic pancreaticoduodenectomy (LPD) as an efficient and feasible surgical technique. However, few studies have investigated its applicability in pancreatic ductal adenocarcinoma (PDAC), and the long‐term efficacy of LPD on PDAC remains unclear. This study aimed to compare the short‐ and long‐term outcomes between LPD and open pancreaticoduodenectomy (OPD) for PDAC. Methods: The data of patients who had OPD or LPD for PDAC between January 2013 and September 2017 were retrieved. Their postoperative outcomes and survival were compared after propensity score matching. Results: A total of 309 patients were included. After a 2:1 matching, 93 cases in the OPD group and 55 in the LPD group were identified. Delayed gastric emptying (DGE), particularly grade B/C DGE, occurred less frequently in the LPD group than in the OPD group (1.8% vs. 36.6%, P < 0.001; 1.8% vs. 22.6%, P = 0.001). The overall complication rates were significantly lower in the LPD group than in the OPD group (49.1% vs. 71.0%, P = 0.008), whereas the rates of major complications were similar (10.9% vs. 14.0%, P = 0.590). In addition, the median overall survival was comparable between the two groups (20.0 vs. 18.7 months, P = 0.293). Conclusion: LPD was found to be technically feasible with efficacy similar to OPD for patients with PDAC.